Aberrant crypt foci: endoscopic assessment and cell kinetics characterization - Figueiredo, Pedro (2008)
Abstract Background and aims Aberrant crypt foci (ACF) are preneoplastic lesions in animal models of colorectal cancer. The aim of the study is to investigate if ACF are involved in human colorectal carcinogenic process and if they can be helpful in predicting the presence of a colorectal neoplasia. Methods The study included, between 2003 and 2005, 182 patients, 62 with adenoma, 55 with colorectal carcinoma, 53 without colorectal lesions, and 12 with nonneoplastic mucosal polyps. The number of rectal ACF was determined by colonoscopy. Proliferation and apoptosis indexes were evaluated by immunohistochemistry in rectal ACF, in normal rectal mucosa, and in carcinomatous tissue. Results The mean number of rectal ACF in patients with rectal neoplasia was 12.64, significantly higher than in patients with neoplastic lesions elsewhere in the colon (p?=?0.01). The apoptosis index in ACF of patients with colorectal carcinoma or adenoma aged 50 years or older was significantly lower than in younger patients (1.3% vs 2.7%, p?=?0.01) and, in patients with carcinoma, lower than in normal mucosa (1.1% vs 2.1%, p?=?0.002). The proliferation index was significantly higher in ACF of patients with colorectal neoplasia aged less than 50 years than in normal mucosa (10.9% vs 7.7%, p?=?0.02). The apoptosis index in ACF foci of patients with carcinoma (1.1%) was significantly lower than in patients without lesions (2.2%) and than in normal mucosa (2%). The mean number of ACF is significantly higher in patients with polyps larger than 1 cm (11.28 vs 6.27, p?=?0.02). Conclusion Aberrant crypt foci probably precede the appearance of neoplasia and may be helpful in predicting the presence of a colorectal neoplastic lesion.